VOCATIONAL STUDENTS' PERCEPTION OF USING YOUTUBE AS A DIGITAL PLATFORM FOR IMPROVING LISTENING COMPREHENSION SKILLS - Anandita Apriliani, Sefrina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study investigates vocational high school students’ perceptions of using YouTube as a digital platform to improve listening comprehension skills in an EFL context. Listening is considered one of the most challenging skills due to limited exposure to authentic English, accent variation, and a lack of engaging learning media. This research employed a descriptive qualitative design involving tenth-grade students at SMK Negeri 5 Surabaya. Data were collected through questionnaires and interviews, and analyzed using thematic analysis. The findings reveal that students generally perceive YouTube positively, as it provides audio-visual support, authentic language exposure, flexibility, and increased motivation. Students reported benefits such as vocabulary acquisition, improved pronunciation, and better contextual understanding. Additionally, YouTube enables personalized learning through features such as replay, subtitles, and adjustable playback speed. However, several challenges were identified, including fast speech, unfamiliar vocabulary, inaccurate or unavailable subtitles, and technical issues such as poor internet connection. Overall, YouTube is considered an effective and engaging platform for improving listening comprehension, although teachers need to guide students in selecting appropriate content and overcoming learning barriers.